Calcium and Vitamin D Supplementation Are Not Associated With Risk of Incident Ischemic Cardiac Events or Death: Findings From the UK Biobank Cohort. (8th February 2018) - Harvey, Nicholas C; D'Angelo, Stefania; Paccou, Julien; Curtis, Elizabeth M; Edwards, Mark; Raisi‐Estabragh, Zahra; Walker‐Bone, Karen; Petersen, Steffen E; Cooper, Cyrus
ABSTRACT: We investigated associations between calcium/vitamin D supplementation and incident cardiovascular events/deaths in a UK population‐based cohort. UK Biobank is a large prospective cohort comprising 502, 637 men and women aged 40 to 69 years at recruitment. Supplementation with calcium/vitamin D was self‐reported, and information on incident hospital admission (ICD‐10) for ischemic heart disease (IHD), myocardial infarction (MI), and subsequent death was obtained from linkage to national registers. Cox proportional hazards models were used to investigate longitudinal relationships between calcium/vitamin D supplementation and hospital admission for men/women, controlling for covariates. A total of 475, 255 participants (median age 58 years, 55.8% women) had complete data on calcium/vitamin D supplementation. Of that number, 33, 437 participants reported taking calcium supplements; 19, 089 vitamin D; and 10, 007 both. In crude and adjusted analyses, there were no associations between use of calcium supplements and risk of incident hospital admission with either IHD, or subsequent death. Thus, for example, in unadjusted models, the hazard ratio (HR) for admission with myocardial infarction was 0.97 (95% confidence interval [CI] 0.79–1.20, p  = 0.79) among women taking calcium supplementation. Corresponding HR for men is 1.16 (95% CI 0.92–1.46, p  = 0.22). After full adjustment, HR (95% CI) were 0.82 (0.62–1.07), p  = 0.14 among women and 1.12 (0.85–1.48), p  = 0.41 among men. Adjusted HR (95% CI) for admission with IHD were 1.05 (0.92–1.19), p  = 0.50 among women and 0.97 (0.82–1.15), p  = 0.77 among men. Results were similar for vitamin D and combination supplementation. There were no associations with death, and in women, further adjustment for hormone‐replacement therapy use did not alter the associations. In this very large prospective cohort, there was no evidence that use of calcium/vitamin D supplementation was associated with increased risk of hospital admission or death after ischemic cardiovascular events. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.